Insights into Metabolic Changes Caused by the Trichoderma virens–Maize Root Interaction - Rabea Schweiger; Fabiola Padilla-Arizmendi; Guillermo Nogueira-López; Michael Rostás; Robert Lawry; Chris Brown; John Hampton; Johanna M. Steyaert; Caroline Müller; Artemio Mendoza-Mendoza (Molecular Plant-Microbe Interactions, 2021)
The interactions of crops with root-colonizing endophytic microorganisms are highly relevant to agriculture, because endophytes can modify plant resistance to pests and increase crop yields. We investigated the interactions between the host plant Zea mays and the endophytic fungus Trichoderma virens at 5 days postinoculation grown in a hydroponic system. Wild-type T. virens and two knockout mutants, with deletion of the genes tv2og1 or vir4 involved in specialized metabolism, were analyzed. Root colonization by the fungal mutants was lower than that by the wild type. All fungal genotypes suppressed root biomass. Metabolic fingerprinting of roots, mycelia, and fungal culture supernatants was performed using ultrahigh performance liquid chromatography coupled to diode array detection and quadrupole time-of-flight tandem mass spectrometry. The metabolic composition of T. virens-colonized roots differed profoundly from that of noncolonized roots, with the effects depending on the fungal genotype. In particular, the concentrations of several metabolites derived from the shikimate pathway, including an amino acid and several flavonoids, were modulated. The expression levels of some genes coding for enzymes involved in these pathways were affected if roots were colonized by the ∆vir4 genotype of T. virens. Furthermore, mycelia and fungal culture supernatants of the different T. virens genotypes showed distinct metabolomes. Our study highlights the fact that colonization by endophytic T. virens leads to far-reaching metabolic changes, partly related to two fungal genes. Both metabolites produced by the fungus and plant metabolites modulated by the interaction probably contribute to these metabolic patterns. The metabolic changes in plant tissues may be interlinked with systemic endophyte effects often observed in later plant developmental stages.